Clinical Outcomes of Modified versus Traditional Technique for the Surgery of Hydatid Cyst of the Liver: A Case Control Study - Fattahi, Asieh Sadat (Middle East J Dig Dis, 2019)
BACKGROUND Echinococcus granulosis is a parasitic infection most commonly involving the liver. Iran is a hyperendemic area for this disease according to WHO. Despite improvements in medical and interventional radiological techniques, surgery remains the gold standard of treatment; however evidence on different surgical modalities were explained. Considering the high population of referring patients presenting to Omid and Ghaem Hospitals, Mashhad, Iran, we decided to compare the complications of our modified technique with routine technique in hydatid cyst surgery. METHODS 56 patients with hydatid cyst of the liver who underwent modified and routine surgical treatment in Ghaem and Omid Hospitals Mashhad, Iran were studied during Aug 2013- Nov 2015. 27 patients underwent modified surgical technique, whereas the remaining 27 patients were treated by using routine surgical method. These two groups of patients were compared with each other according to their postoperative length of hospital stay and resulting complications. RESULTS The mean age of our patients was 41 years. 27 patients were male and 29 were female. Our results showed no statistically significant difference regarding the incidence of postoperative complications between the two groups. However, mean length of hospital stay was significantly different between the groups (4.5 ± 1.87 and 7.6 ± 2.25 days, respectively, p < 0.001). CONCLUSION The method of modified surgery with closed cyst drainage, which does not use external drains, is a safe surgical modality in the treatment of hydatid cyst disease of the liver if applied properly on appropriate patients.